2017
DOI: 10.3917/clini.014.0092
|View full text |Cite
|
Sign up to set email alerts
|

Deux principes dans l’élaboration psychique institutionnelle des changements : pensée binaire et pensée qualitative

Abstract: Le concept de « résistance au changement » (K. Lewin) ne questionne guère la qualité du changement, il s’intéresse essentiellement à la réaction de tout groupe à tout changement. Les auteurs qui ont dialogué avec K. Lewin, en particulier W. Bion, E. Jaques, J. Bleger, vont en partie lui emboîter le pas tout en repérant les enjeux psychiques inconscients de cette résistance. Partant de deux situations de clinique institutionnelle, l’auteur fait ressortir que le plus souvent les équipes se positionnent en tout o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…This was the case in Lewin's "Kriegslandschaft", his programmatic work published in 1917, in which he showed that, while marching on a field, the soldier will look at the field differently in times of peace than in times of war (Bäumler, 2017;Keller, 2016;Previšić, 2016;Wieser, 2014). Starting from this idea, Lewin advanced his theory claiming that a field exists in a state of quasi-stationary equilibrium: it is neutral when there are no forces acting upon it or when the acting forces annihilate themselves (Autissier et al, 2018;Rouchy, 2009;Stützle-Hebel, Antons, 2017;Talpin, 2017). However, this neutrality is rarely met in real life, when driving forces and restraining forces impact upon a certain situation (Damian, Susanu, 2018;Watkins, Lundberg, 1998).…”
Section: Field Theory and Social Changementioning
confidence: 99%
“…This was the case in Lewin's "Kriegslandschaft", his programmatic work published in 1917, in which he showed that, while marching on a field, the soldier will look at the field differently in times of peace than in times of war (Bäumler, 2017;Keller, 2016;Previšić, 2016;Wieser, 2014). Starting from this idea, Lewin advanced his theory claiming that a field exists in a state of quasi-stationary equilibrium: it is neutral when there are no forces acting upon it or when the acting forces annihilate themselves (Autissier et al, 2018;Rouchy, 2009;Stützle-Hebel, Antons, 2017;Talpin, 2017). However, this neutrality is rarely met in real life, when driving forces and restraining forces impact upon a certain situation (Damian, Susanu, 2018;Watkins, Lundberg, 1998).…”
Section: Field Theory and Social Changementioning
confidence: 99%